Inhibition of human cytochromes P450 2A6 and 2A13 by flavonoids, acetylenic thiophenes and sesquiterpene lactones from Pluchea indica and Vernonia cinerea - Supattra Boonruang; Khanistha Prakobsri; Phisit Pouyfung; Ekaruth Srisook; Aruna Prasopthum; Pornpimol Rongnoparut; Songklod Sarapusit (Taylor & Francis Group, 2017)
The human liver cytochrome P450 (CYP) 2A6 and the respiratory CYP2A13 enzymes play role in nicotine metabolism and activation of tobacco-specific nitrosamine carcinogens. Inhibition of both enzymes could offer a strategy for smoking abstinence and decreased risks of respiratory diseases and lung cancer. In this study, activity-guided isolation identified four flavonoids 1-4 (apigenin, luteolin, chrysoeriol, quercetin) from Vernonia cinerea and Pluchea indica, four hirsutinolide-type sesquiterpene lactones 5-8 from V. cinerea, and acetylenic thiophenes 9-11 from P. indica that inhibited CYP2A6- and CYP2A13-mediated coumarin 7-hydroxylation. Flavonoids were most effective in inhibition against CYP2A6 and CYP2A13, followed by thiophenes, and hirsutinolides. Hirsutinolides and thiophenes exhibited mechanism-based inhibition and in irreversible mode against both enzymes. The inactivation kinetic KI values of hirsutinolides against CYP2A6 and CYP2A13 were 5.32-15.4 and 0.92-8.67 µM, respectively, while those of thiophenes were 0.11-1.01 and 0.67-0.97 µM, respectively.